Lightweight authentication method for network interconnection control protocols - Bo LU; Yun LIU; Jie ZHANG; Yueming LU (网络与信息安全学报)
As network interconnection controls are required for the space-earth integrated network and the limited resources are not suitable for high computing complexity degree authentication methods,a lightweight authentication method for network interconnection control protocols is proposed.Through the calculation of limited resources,using the idea of random fill,It design and implement public key encryption and signature algorithm which is components of the networks interconnection control authentication protocol.Formal analysis tool Scyther is used to analyze the security of the protocol.Comparing with other secure communication protocols,the method can meet the requirements of resource-constrained networks and ensure the safety.